Hadronic structure in the decay τ-→π-π0ντ - Anderson, S; Frolov, V; Kubota, Y; Lee, S; Mahapatra, R; O'Neill, J; Poling, R; Riehle, T; Smith, A; Ahmed, S; Alam, MS; Athar, S; et al. (2000)
We report on a study of the invariant mass spectrum of the hadronic system in the decay τ-→π-π0ντ. This study was performed with data obtained with the CLEO II detector operating at the CESR e+e- collider. We present fits to phenomenological models in which resonance parameters associated with the ρ(770) and ρ(1450) mesons are determined. The π-π0 spectral function inferred from the invariant mass spectrum is compared with data on e+e-π+π- as a test of the conserved vector current theorem. We also discuss the implications of our data with regard to estimates of the hadronic contribution to the muon anomalous magnetic moment. ©2000 The American Physical Society.